Traveling planning concepts revisited: how they land and why it matters - Gómez Lucía; Oinas Päivi (Taylor & Francis, 2022)
What constitutes the “landing” of “traveling planning concepts” (TPCs) in new places remains conceptually elusive in the literature. To explore this process, this paper proposes a multidimensional conceptual framework that identifies key recurring activities during landing. The framework is applied to a qualitative analysis of the ongoing development of an innovation district in the rising yet unequal city of Medellín. The analysis reveals a process during which introductions of the concept with add-on components were legitimized based on translations adjusting it to the local circumstances, while governance procedures coordinated mandates for action, and a version of the concept gradually materialized. These recurring activities constituted mechanisms that generated the progression of landing through subsequent phases. In Medellín, the TPC resulted in a distributed model that corresponds neither to the prevailing innovation district concept nor the locally intended socially inclusive version. This paper contributes by showing why the analysis of landing processes is key to understanding whether, how, and in what form traveling planning concepts appear in new destinations. This novel framework enables a systematic and comprehensive identification of the causal process comprising the mechanisms that make both the TPC landing and the version of the TPC it produces unique.